The Degree of Practice Secondary Schools Principals in Deir Alla in Jordan The Managing by Values from the Perspectives of Teachers - Daas, Shereen Jamal (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to identifying the degree of practice secondary schools principals in Deir Alla of Jordan the managing by values from the perspectives of teachers. The population of the study included all (305) teachers. The study sample consisted of 145 teacher, And 48% of the secondary school study population in Deir Alla District for the academic year 2019/2020 who were selected using the simple random method. To achieve the objectives of the study, the researcher used the descriptive survey method and developed the study instrument, which was a questionnaire consisting of (41) items in five dimensions. The results revealed that of practicing managing by values by high schools principals was high, with a mean score of (4.15). The results showed statistically significant differences at the level (α≤ 0.05) between the mean scores of respondents for the dimension of "justice values" according to the gender variable, and in favor of females. There were not any statistically significant differences at the level (α≤ 0.05) between the mean scores of the responses in the dimensions of (Experience, Specialization, Academic Qualification). In light of the study results, the researcher recommended identifying a set of basic organizational values and special to schools within the Ministry of Education, and circulating them in the field. The study recommended defining the most important areas and practices of these values through periodic publications issued by the Ministry that include the vision and mission based on values.